Detection and Characterisation of Endosymbiont Wolbachia (Rickettsiales: Anaplasmataceae) in Elaeidobius kamerunicus (Coleoptera: Curculionoidea), Pollinating Agent of Oil Palm, and Its Relationships between Populations - Mohd Nur Azad Rushidi,; Muhammad Luqman Hakim Azhari,; Salmah Yaakop,; Izfa Riza Hazmi, (Tropical Life Sciences Research, 2023)
Elaeidobius kamerunicus is the most efficient pollinator of oil palm. Wolbachia is an endosymbiotic bacteria associated with E. kamerunicus that has a potential to affect the fecundity and fitness of the E. kamerunicus. Despite their importance, no studies have been conducted to investigate its prevalence in E. kamerunicus. The objectives of this study were to detect and characterize Wolbachia in E. kamerunicus and determine the phylogenetic relationship of Wolbachia strains that infect E. kamerunicus by using three genetic markers namely Filamenting temperature-sensitive mutant Z (ftsZ), Chaperonin folding protein (groEL), and Citrate Synthase Coding Gene (gltA). DNA was extracted from 210 individuals of E. kamerunicus and the Wolbachia infections were detected using the wsp marker. The infected samples (n = 25, 11.9%) were then sequenced using ftsZ, gltA and groEL markers for strain characterisation. In this study, a combination of four markers was used to construct the phylogeny of Wolbachia. Similar topologies were shown in all trees; Neighbour-Joining (NJ), Maximum Parsimony (MP), and Bayesian Inference (BI), which showed the mixing of individuals that harbor Wolbachia between populations. Interestingly, Wolbachia on E. kamerunicus was claded together with the species Drosophila simulans under supergroup B. This is the first report of Wolbachia infecting E. kamerunicus which is very valuable and significant as one of the parameters to evaluate the quality of the E. kamerunicus population for sustaining its function as a great pollinator for oil palm.